The application of 3D bioprinting in urological diseases. (December 2022) - Xu, Kailei; Han, Ying; Huang, Yuye; Wei, Peng; Yin, Jun; Jiang, Junhui
Abstract: Urologic diseases are commonly diagnosed health problems affecting people around the world. More than 26 million people suffer from urologic diseases and the annual expenditure was more than 11 billion US dollars. The urologic cancers, like bladder cancer, prostate cancer and kidney cancer are always the leading causes of death worldwide, which account for approximately 22% and 10% of the new cancer cases and death, respectively. Organ transplantation is one of the major clinical treatments for urological diseases like end-stage renal disease and urethral stricture, albeit strongly limited by the availability of matching donor organs. Tissue engineering has been recognized as a highly promising strategy to solve the problems of organ donor shortage by the fabrication of artificial organs/tissue. This includes the prospective technology of three-dimensional (3D) bioprinting, which has been adapted to various cell types and biomaterials to replicate the heterogeneity of urological organs for the investigation of organ transplantation and disease progression. This review discusses various types of 3D bioprinting methodologies and commonly used biomaterials for urological diseases. The literature shows that advances in this field toward the development of functional urological organs or disease models have progressively increased. Although numerous challenges still need to be tackled, like the technical difficulties of replicating the heterogeneity of urologic organs and the limited biomaterial choices to recapitulate the complicated extracellular matrix components, it has been proved by numerous studies that 3D bioprinting has the potential to fabricate functional urological organs for clinical transplantation and in vitro disease models. Graphical abstract: Image 1 Highlights: Outline the advantages and characteristics of 3D printing compared with traditional methods for urological diseases. Guide the selection of 3D bioprinting technology and material in urological tissue engineering. Discuss the challenges and future perspectives of 3D bioprinting in urological diseases and clinical translation.